국내 잣나무림의 하층식생 유형별 바이오매스 추정 상대생장식 개발 - 김다영; Dayoung Kim; 신중훈; Joonghoon Shin; 정형식; Hyungsik Jeong; 한희; Hee Han (한국산림과학회지, 2025)
본 연구는 국내 잣나무림의 하층식생 유형별 바이오매스를 추정하기 위한 상대생장식을 개발하고자 하였다. 이를 위해 경기도 태화산에 위치한 61년생 잣나무림에서 표본조사를 실시하고, 하층식생을 어린교목과 초본층으로 구분하여 개체 단위 총 바이오매스를 추정하는 회귀모형을 개발하였다. 어린 교목에서는 근원직경의 제곱과 식생 높이의 곱이 가장 유효한 독립변수로 도출되었으며(adjusted R 2 = 0.9506), 초본층에서는 줄기수와 줄기길이를 조합하여 바이오매스를 추정하는 것이 가장 효과적이었다(adjusted R 2 = 0.7168~0.8580). 반면, 식생 높이를 단독 독립변수로 사용할 경우, 측정의 어려움과 환경적 변동성에 따른 불확실성이 증가하면서 추정력이 낮아지는 경향을 보였다(adjusted R 2 = -0.0721~0.4392). 또한, 바이오매스 상대생장식에 혼합효과 모형을 적용함으로써 식생 유형별로 개별 모형을 구축하지 않더라도 유형 간 차이를 효과적으로 반영할 수 있음을 확인하였다. 이를 통해 표본 크기에 따른 제약을 완화하는 동시에 바이오매스 추정의 정확성을 향상시킬 수 있었다. 본 연구는 국내 산림의 하층식생 바이오매스 평가를 위한 기초자료를 제공하며, 향후 다양한 임분 형태와 수종을 대상으로 연구를 확장함으로써 산림자원 및 탄소량 평가의 정확성을 제고하는 데 기여할 것으로 기대된다. This study aimed to develop allometric equations to estimate the biomass of understory vegetation by vegetation type in Korean pine forests. A field survey was conducted in a 61-year-old Korean pine forest on Mt. Taehwa in Gyeonggi Province. Understory vegetation was classified as young trees or herbaceous layers, and regression models were developed to estimate the total biomass at the individual plant level for each vegetation type. For young trees, the product of the diameter at the root collar squared and height emerged as the most effective predictor (adjusted R 2 = 0.9506). For the herbaceous layer, a combination of stem number and stem length provided the most accurate biomass estimates (adjusted R 2 = 0.7168~0.8580). Conversely, the use of vegetation height alone as an independent variable achieved low estimation performance because of measurement difficulties and environmental influences (adjusted R 2 = -0.0721~0.4392). Furthermore, the application of mixed-effects models to the biomass allometric equations enabled the integration of differences among vegetation types within a single model. This approach mitigated sample size constraints while improving the accuracy of biomass estimation. This study provides fundamental data for assessing understory biomass in Korean forests, and these findings are expected to help enhance the accuracy of forest resource and carbon stock evaluations by expanding future research to encompass diverse stand structures and tree species.